1988
DOI: 10.3164/jcbn.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Improved Sulfatide-Containing Liposomes as Carriers of Adriamyein

Abstract: SummaryVarious molar ratios of the constituents of sulfatidecontaining liposomes (egg phosphatidylcholine, cholesterol, and sulfatide) were examined with respect to liposomal efficiency to entrap adriamycin (ADM) and to the tissue distribution. Among the ratios of the constituents examined, 5 : 4 : 1 was the best in terms of entrapment efficiency for both multilamellar vesicles (MLV) and small unilamellar vesicles (SUV). Tissue distribution studies of liposome-entrapped ADM showed that the blood clearance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Various negatively charged lipids have been adopted as constituents of liposomes for their efficient entrapment of ADM. In our previous studies [12,14], CSE was found to be the most suitable constituent to obtain negatively charged liposomes for efficient entrapment of ADM. For clinical application, however, a less expensive and more easily obtainable constituent is desirable. Thus we made an extensive survey and finally chose Cho1SO4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various negatively charged lipids have been adopted as constituents of liposomes for their efficient entrapment of ADM. In our previous studies [12,14], CSE was found to be the most suitable constituent to obtain negatively charged liposomes for efficient entrapment of ADM. For clinical application, however, a less expensive and more easily obtainable constituent is desirable. Thus we made an extensive survey and finally chose Cho1SO4.…”
Section: Discussionmentioning
confidence: 99%
“…For effective entrapment of ADM many kinds of negatively charged lipids such as egg phosphatidylserine (PS) [7,8], dicetylphosphate (DCP) [9,10], cardiolipin [11], and sulfatide (CSE) [12,13] have been utilized to provide negative charge to the liposomal membranes. In previous studies, we found that the CSE-containing liposomes composed of egg phosphatidylcholine (PC), cholesterol (Chol), and CSE in a molar ratio of 5 : 4 : 1 were the best in terms of entrapment efficiency for ADM and that the liposomes acted not only to reduce the incorporation of ADM into the heart but also to increase the level of ADM in tumors [14,15]. For clinical application of these vesicles, however, it is desirable to obtain less expensive material that can be a substitute for CSE.…”
mentioning
confidence: 99%
“…Preparation of liposomes entrapping ADM. Liposomes entrapping ADM were prepared according to Takano et al [13]. Briefly, a mixture of lipids (50 1u mot) consisting of PC, Chol, and sulfatide (molar ratio, 5 : 4 : 1) was dissolved in chloroform-methanol (2: 1, v/v), and the solvent was removed under reduced pressure with a rotary evaporator to form a thin lipid film in the flask.…”
Section: Methodsmentioning
confidence: 99%
“…However, its clinical application is limited by its cardiotoxicity that arises from cumulative treatment [2][3][4][5]. For reduction of such toxicity, entrapment of ADM into negatively charged liposomes has been successfully done without a decrease in its antineoplastic activity [6][7][8][9][10][11][12][13][14][15]. In particular, liposomes composed of egg yolk phosphatidylcholine (PC), cholesterol (Chol), and sulfatide in a molar ratio of 5 : 4: 1 can entrap ADM efficiently and act to reduce the accumulation of ADM in the heart and to increase the level of ADM in the tumor and liver [13 , 14].…”
mentioning
confidence: 99%
“…lar, we found that liposomes composed of egg phosphatidylcholine (PC), cholesterol (Chol), and sulfatide (CSE) in a molar ratio of 5 : 4 : 1 can entrap ADM efficiently and that they act to reduce the incorporation of ADM in the heart and to increase the level of ADM in tumors [13,14]. For clinical use of such liposomes, a less expensive and more easily obtainable negatively charged lipid than CSE is needed.…”
mentioning
confidence: 99%